A critical review on wear and corrosion of carbide free bainitic steel. Issue 1 (June 2021) - Sharma, Siddharth; Tripathi, Ajay; Dwivedi, Ravi Kumar; Kumar, Rajan; Agarwal, Anupma
Abstract: Different research on wear and corrosion of CFB (carbide free bainitic steel) over the past two decades has enabled a better understanding and advanced applications of CFB steel. With the help of advanced testing techniques, and equipment the detailed study of microstructure and nanostructured steels has been possible. The earlier years were focused on comparison of the bainite steel with the steel which is quenched and tempered (QT) for identifying the wear tendencies and comparison between carbon free bainite and martensite for the corrosive behavior of the carbide free bainitic steel. Later the trend shifted towards the nanostructured analysis from microstructure analysis with the improvement in the instruments. Advancements like HT-CAT i.e., high temperature continuous abrasion tester have an important role to play, the mechanism of material removal rate studied. There has also been development in alloying the bainite to reduce the corrosion rate and give more strength. Current trends in the form of study of wear and corrosion of carbide free bainitic steel and future needs are discussed hereby.